Changing perceptions of general health in the Kayseri Province, Turkey in 2004 and 2017: A population-based study - Senol, Vesile; Elmali, Ferhan; Cetinkaya, Fevziye; Nacar, Melis (Frontiers in Public Health, 2023)
Aim: Self-rated health (SRH) and health-related quality of life (HRQoL) have closely related outcomes to measure general health status in community-based studies. The aim of this study was to determine changes in the self-perceived overall health of people and affected factors by comparing the findings of two studies conducted in the same research area. Methods: Both studies were conducted using the same measurement tools in households determined by random technique in the same research areas. The first and second study was conducted with 1304 and 1533 people residing in 501 and 801 households in 2004 and 2017, respectively. The demographic data form, Nottingham Health Profile (NHP), and a single-item SRH question were used for the data collection. Results: The rate of good SRH increased from 56% to 70% while the average NHP score decreased from 30.87 to 20.34. Predictors for negative health perception are presence of chronic diseases (3.4-2.7 fold), being female (1.4-1.5 fold), and primary school graduation (2.7-2.8 fold) in both 2004 and 2017. Living 500-1000 m away from the nearest health facility was the main protective variable against poor SRH. Conclusions: Good SRH and HRQoL increased significantly over time. Chronic diseases, education, and gender were the strongest predictors of poor SRH.